Communication and information technology in society - Kowal, Jolanta; Wawrzak-Chodaczek, Miroslawa; Kuzio, Anna (Cambridge Scholars Publishing, 2015)
This book investigates the psycho-social and pedagogical aspects of the development of communication and its media. It represents a major contribution to the discussion on the role of the media in the modern world and explores a number of problems in the fields of the social sciences, cultural studies and education. The views presented here offer insights from European countries in transition, and reflect the fact that globalization accounts for the culturally diverse societies in which many ...